Synthesis of a highly electron-deficient, water-stable, large ionic box: multielectron accumulation and proton conductivity - Shukla, Jyoti; Illathvalappil, Rajith; Kumar, Sharvan; Chorol, Sonam; Pandikassala, Ajmal; Kurungot, Sreekumar; Mukhopadhyay, Pritam (Organic Letters, 2022)
pi-acidic boxes exhibiting electron reservoir and proton conduction are unprecedented because of their instability in water. We present the synthesis of one of the strongest electron-deficient ionic boxes showing e(-) uptake as well as proton conductivity. Two large anions fit in the box to form anion-pi interactions and form infinite anion-solvent wires. The box with NO3-center dot center dot center dot water wires confers high proton conductivity and presents the first example that manifests redox and ionic functionality in an organic electron-deficient macrocycle.